Experimental evaluation of an industrial technique for the approximation of software functional size - Almakadmeh, Khaled; Abran, Alain (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The Early & Quick sizing techniques, built based on ISO standards, have been proposed to derive an early approximation of software functional size when only high-level and incomplete requirements specifications are available. In the literature, there is a lack of research to evaluate the performance of such approximation sizing methods. This paper presents an experimental study to evaluate their reproducibility and accuracy. The experimental results show both poor reproducibility and large inaccurate approximations. In particular, the analysis of the findings indicates that the practitioners could not classify the functional requirements specifications in accordance to their levels of granularity using the rules and the concepts of the Early & Quick COSMIC technique.